MON-496 Bone Mineral Density improvement with Vitamin Dsupplementation in a Case Of Childhood Hypophosphatasia - Babar, Ghufran (J Endocr Soc, 2019)
Hypophosphatasia is associated with defective mineralization of bone with possible teeth involvement with low activity of serum and bone alkaline phosphatase. It is caused by a mutations in the TNSALP gene. It is usually life-threatening when it presents within the first six months of life. It has six subtypes: perinatal lethal, prenatal benign, infantile, childhood, adulthood and odontohypophosphatasia. Childhood hypophosphatasia, defined as onset of symptoms between six months and eighteen years, can present as rickets, pain, decreased mobility, deficits of growth, and fractures. CASE REPORT: A 3-year-old child presented in the Endocrinology clinic due to premature loss of her four lower incisors and x-rays showed significant bone loss in the mandible. She also had reduced serum alkaline phosphatase activity. She was diagnosed with Childhood Hypophosphatasia, which was confirmed by genetic investigation. The molecular study showed that the patient is heterozygous for a c.1133A greater than T (p.Asp378Val) variation in exon 10 of the ALPL gene. The child also had a low Vitamin D level of 23 ng/ml (30-100), the Dexa-scan showed a low bone mineral density with a z-score of -2.4 SD below the mean in the distal femur area, which responded to Vitamin D supplementation and oral calcium therapy and normalized. The child did not have any fractures about 9 years after initial diagnosis. Bone turnover markers including Osteocalcin and N-telopeptide levels also normalized. The premature loss of teeth stopped. The child grew and gained weight as expected. CONCLUSION: Hypophosphatasia is suspected in a child with premature loss of deciduous teeth. Testing for a reduced serum alkaline phosphatase activity should be done. The children can be associated with rickets and low vitamin D. Improvement in low bone mineral density is possible with giving adequate doses of vitamin D, calcium and doing non-contact sports. Monitoring of bone mineral density can be done on a yearly basis.